2019
DOI: 10.3390/ijerph16050861
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Obesity, Obesogenic Environments, and Structural Racism Vary by County-Level Racial Composition

Abstract: Obesity rates in the U.S. are associated with area-level, food-related characteristics. Studies have previously examined the role of structural racism (policies/practices that advantaged White Americans and deprived other racial/ethnic minority groups), but racial inequalities in socioeconomic status (SES) is a novel indicator. The aim of this study is to determine the associations between racial inequalities in SES with obesity and obesogenic environments. Data from 2007–2014 County Health Rankings and 2012–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
5
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 85 publications
(153 reference statements)
2
62
5
3
Order By: Relevance
“…While this result supports research on obesogenic environments and property value (12,37), we found little evidence of a similar association between housing wealth and obesity among Black women and men. This finding could be the result of discriminatory practices at multiple stages of purchasing a home that constrain Black families from moving into more desirable-and less obesogenicneighborhoods (10,12). Thus, future research should extend this study by considering how residential quality and racial segregation moderate the relationship between housing wealth and obesity.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…While this result supports research on obesogenic environments and property value (12,37), we found little evidence of a similar association between housing wealth and obesity among Black women and men. This finding could be the result of discriminatory practices at multiple stages of purchasing a home that constrain Black families from moving into more desirable-and less obesogenicneighborhoods (10,12). Thus, future research should extend this study by considering how residential quality and racial segregation moderate the relationship between housing wealth and obesity.…”
Section: Discussioncontrasting
confidence: 58%
“…Housing wealth is the largest contributor to net worth and grows as a financial resource in midlife (4,10). With respect to obesity, prior research has found that obesogenic environments (e.g., areas perceived as proximate to crime, heavy traffic, liquor stores, and fast food) are associated with lower property values, and property values are negatively associated with obesity and BMI (11)(12)(13). Rehm et al (13) examined the assessed value of homes in a Washington county and found that women with property in the bottom quartile were 3.4 times more likely to experience obesity than women in the top quartile.…”
Section: Introductionmentioning
confidence: 99%
“…Home value had a particularly large association with obesity for white women and men. Although this result supports research on obesogenic environments and property value , we found little evidence of a similar association between home value and obesity among black women and men. This finding could be the result of discriminatory practices at multiple stages of purchasing a home that constrain black families from moving into more desirable (and less obesogenic) neighborhoods .…”
Section: Discussioncontrasting
confidence: 57%
“…Although this result supports research on obesogenic environments and property value , we found little evidence of a similar association between home value and obesity among black women and men. This finding could be the result of discriminatory practices at multiple stages of purchasing a home that constrain black families from moving into more desirable (and less obesogenic) neighborhoods . Thus, future research should extend this study by considering how residential quality and racial segregation moderate the relationship between home value and obesity.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation